2017
DOI: 10.6026/97320630013360
|View full text |Cite
|
Sign up to set email alerts
|

Ymr210wp leads to the accumulation of phospholipids and steryl esters in yeast

Abstract: Ymr210w was identified as a MAG (Monoacylglycerol) lipase. The accumulation of the phospholipids in the ymr210wΔ was not clearly understood. It was expressed in S. cerevisiae using pYES2/CT vector and His-tag purified recombinant protein confirmed TAG lipase activity. To further evaluate the role of YMR210w, ester hydrolase activity was also confirmed with pNP-acetate, pNP-butyrate and pNP - palmitate. GC-MS lipid profiling of ymr210wΔ showed an increase in the 15:0 Pentadecanoic acid by 76% among the total li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…But it has been shown that it has the same catalytic site, which is the most important domain and where all the activity takes place for the formation of these aromas. As a result, enzymes encoded by this gene have been created and are actively involved in the production of ethyl acetate and isoamyl acetate in this yeast [Manda et al, 2017;Naresh Kumar et al, 2018]. On J Mol Microbiol Biotechnol 2019;29:1-9 DOI: 10.1159/000507551 the other hand, the enzymes encoded by the EHT1 and EAT1 genes participate in the synthesis of aromas such as ethyl ethanoate, ethyl hexanoate, and ethyl decanoate, among others [Celińska et al, 2018;Löbs et al, 2017].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But it has been shown that it has the same catalytic site, which is the most important domain and where all the activity takes place for the formation of these aromas. As a result, enzymes encoded by this gene have been created and are actively involved in the production of ethyl acetate and isoamyl acetate in this yeast [Manda et al, 2017;Naresh Kumar et al, 2018]. On J Mol Microbiol Biotechnol 2019;29:1-9 DOI: 10.1159/000507551 the other hand, the enzymes encoded by the EHT1 and EAT1 genes participate in the synthesis of aromas such as ethyl ethanoate, ethyl hexanoate, and ethyl decanoate, among others [Celińska et al, 2018;Löbs et al, 2017].…”
Section: Resultsmentioning
confidence: 99%
“…This reaction requires the catalytic action of esterases, which are proteins with dual nature, since they can act as ethanol Oacyltransferases and as thioesterases (Eht1p, Eeb1p) [Ichikawa et al, 1991;Yin et al, 2019;Zelner et al, 2013]. However, Mgl2p is a protein that also possesses lipase activity and therefore is responsible for maintaining cellular lipid balance [Gajewski et al, 2017;Manda et al, 2017;Robinson et al, 2014]. The function of the AEATases is to obtain the CoA of medium chain fatty acid esters by hydrolyzing them, and to a lesser degree participating in their formation by transesterification.…”
Section: Esterasesmentioning
confidence: 99%
“…Tgl3p was discovered in LDs through proteomic studies (Athenstaedt and Daum, 2003). Another lipase described in this yeast was Ypr147cp, which is also located in LDs, playing an important role in the mobilization of TAGs from LDs (Manda et al, 2017). It is known that one of the major TAG lipases, Tgl3p, preferentially uses TAGs that contain C14:0, C16:0 and C26:0 fatty acids (Athenstaedt and Daum, 2003).…”
Section: Discussionmentioning
confidence: 99%